(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the theoretical and practical aspects of developing compositional competence in future visual arts teachers through interactive teaching methods. The essence and content of compositional competence, its structural components, and its role in painting classes are substantiated from a scientific and pedagogical perspective. Furthermore, the didactic potential of interactive methods such as brainstorming, small group work, problem-based learning, reflection, and project-based learning in developing compositional thinking is highlighted. The research findings indicate that the use of interactive methods contributes to the development of independent thinking, creative approach, aesthetic taste, and analytical skills among students. The article also proposes mechanisms for the step-by-step development of compositional competence and provides methodological recommendations.